From Metagenomics to Discovery of New Viral Species: Galium Leaf Distortion Virus, a Monopartite Begomovirus Endemic in Mexico - Guevara-Rivera, Enrique A.; Rodríguez-Negrete, Edgar A.; Aréchiga-Carvajal, Elva T.; Leyva-López, Norma E.; Méndez-Lozano, Jesús (Frontiers in Microbiology, 2022)
Begomoviruses (Family Geminiviridae) are the major group of emerging plant viruses worldwide. The knowledge of begomoviruses is mostly restricted to crop plants systems, nevertheless, has been described that non-cultivated plants are important reservoirs and vessels of viral evolution leading to the emergence of new diseases. High-throughput sequencing (HTS) has provided a powerful tool to speed up the understanding of molecular ecology and epidemiology of plant virome as well as for the discovery of new viral species. In this work, using earlier metagenomic libraries data mining, followed by geminivirus-related signature single plant searching and RCA-based full-length viral genome cloning, and based on phylogenetic analysis, the genomes of two isolates of a novel monopartite begomovirus species tentatively named Galium leaf distortion virus (GLDV) infecting non-cultivated endemic plant Galium mexicanum were identified in Colima, Mexico. Analysis of the genetic structure of both isolates (GLDV-1 and GLDV-2), revealed that GLDV genome displays a DNA-A-like structure shared with New World (NW) bipartite begomoviruses; nonetheless, phylogenetic analysis using representative members of the main begomovirus American clades for tree construction, grouped both GLDV isolates in the clade of the monopartite NW begomovirus, ToLDeV. A comparative analysis of viral replication regulatory elements showed that GLDV-1 isolate possesses an array and sequence conservation of iterons typical of NW begomovirus infecting Solanaceae and Fabaceae families. Interestingly, GLDV-2 showed iteron sequences described only in monopartite begomovirus from OW belonging to sweepovirus clade which infects plants of the Convolvulaceae family. In addition, the Rep Iteron Related Domain (IRD) of both isolates display the FRVQ or FRIS amino acid sequences, corresponding to NW and sweepo begomovirus clades for GMV-1 and GMV-2, respectively. Finally, lacking of GLDV DNA-B segment (tested by molecular detection, and biological assays using GLDV-1/2 infectious clones) confirmed the monopartite nature of GLDV. This is the first time that a monopartite begomovirus is described in Mexican ecosystems and “in silico” geometagenomics analysis indicates that is restricted to a specific region. These data revealed additional complexity in monopartite begomovirus genetics and geographic distribution, and highlights the importance of metagenomic approaches to understanding global virome ecology and evolution